A review of asphaltic crack healing approaches and Its mechanism - Mohd Fahmi Haikal, Mohd Ghazali; Mohd Rosli, Mohd Hasan; Anasyida, Abu Seman; Dorett, Dillon Dipagk; Najib, Mukhtar; Putra Jaya, Ramadhansyah (Hindawi Publishing Corporation, 2021)
(e concept of self-healing has an excellent potential to extend the life of asphalt pavement. (is technology can be considered a sustainable technology due to its ability to reduce the utilization of asphalt mixture production materials used for road maintenance, polluting the environment. It is a complex physicochemical process wherein the molecular diffusion healing mechanisms in asphalt materials are inspired by self-healing polymeric systems, which describe the self-recovery behaviors based on polymer chain dynamics. Several methods have been adopted to improve the self-healing of asphalt, one of which is induction healing. It is the process of heating the asphalt pavement incorporated with an electrically conductive material such as steel fibers, wherein asphalt healing is undertaken via electric field induction. Induction healing via induction heating occurs with eddy current where the electric current flows within the conductive fibers when magnetically susceptible under the magnetic field. Microwave heating is another self-healing method similar to induction in which magnetic radiation is employed to treat asphalt mixtures instead of the electric field-induced induction healing processes. (e conductive fibers can absorb the electromagnetic (EM) waves to convert them into heat energy through doublet polarization, interface polarization, and electrical conduction dissipation when placed in the microwave field. (ese two types of heating systems, which are induction heating and microwave heating, are compared and discussed thoroughly in this study. Finally, some recommendations for the future development of selfhealing asphalt are proposed.